2007
DOI: 10.1021/jo701939c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Notions of Aromaticity and Antiaromaticity: Phenalenyl Ions versus Fluorenyl Ions

Abstract: The dications 6, 7, and 8 and dianions 9, 10, and 11 of the bistricyclic aromatic enes bifluorenylidene (1), 1,1'-biphenalenylidene (2), and 9-(9H-fluoren-9-ylidene)-1H-phenalene (4), as well as monocations 12a and 13a and monoanions 14a and 15a of phenalene (3) and fluorene (5), were subjected to a systematic DFT and ab initio study. B3LYP and MP2 methods were employed to estimate the relative aromaticity/antiaromaticity of these ions, using energetic, magnetic, and structural criteria. The couplings of monoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…[1][2][3][4][5][6] In 1980, Olah and Schleyer et al described unsuccessful attempts to isolate 1 in superacidic media: "We were not able to generate the parent 9-fluorenyl cation 1-H by slowly adding SO 2 or SO 2 ClF solutions of possible precursors… at À120 8C. The resulting solutions immediately became dark and unidentifiable polymeric materials were formed".…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] In 1980, Olah and Schleyer et al described unsuccessful attempts to isolate 1 in superacidic media: "We were not able to generate the parent 9-fluorenyl cation 1-H by slowly adding SO 2 or SO 2 ClF solutions of possible precursors… at À120 8C. The resulting solutions immediately became dark and unidentifiable polymeric materials were formed".…”
mentioning
confidence: 99%
“…Furthermore, the NICS 1 value of PLY 0 (À5.8 ppm) is also consistent with that previously (À6.2 ppm) found by Pogodin. 57 In the neutral compounds, substitution of the central carbon by tetrel atoms results in less negative NICS values. This is also true for icosagen substitutions and for pnictogen atoms (only for NICS 0, þ1 and þ2).…”
Section: Nmr Propertiesmentioning
confidence: 99%
“…56 In addition, cationic derivatives of phenalenyl have been studied and the aromatic behaviour of such systems has also been described. 57 The problem of aromaticity in radical species is particularly interesting. 15,58e62 Mandado et al studied the differences in aromaticity in monocyclic radicals and reported that it is necessary to take into account the a and b electron-densities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that various dispute has been getting along with the development of this concept, certainly, we must admit that aromaticity has been playing an important role in interpreting molecular properties for many compounds [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The substantial energy stabilization, bond length equalization, unusual reactivity, and characteristic spectroscopic features as well as distinctive magnetic properties are some important aspects with which researchers depict this special concept.…”
Section: Introductionmentioning
confidence: 99%